1989
DOI: 10.1007/bf00965929
|View full text |Cite
|
Sign up to set email alerts
|

Changes with darkness in regional brain 5-hydroxytryptamine and 5-hydroxyindole acetic acid: Local differences with pinealectomy, sham surgery, and melatonin

Abstract: Brain regional 5-HT (5-hydroxytryptamine) and 5-HIAA (5-hydroxyindole-3-acetic acid) concentrations in male LE rats at three times were measured by a fluorescence method, to evaluate effects of intracranial surgery and administration of melatonin on the changes in these compounds during the first part of the dark phase of the daily cycle in a fixed 12:12 L:D photoperiod. Early surgical pinealectomy or a similar but sham intracranial surgery, led to delay in darkness-associated fall in frontal cortical and stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Melatonin, the major secretory product of the pineal gland, has been known to interact with neuroendocrine axis [2] and circadian rhythms [1]. Recently, several studies demonstrated that melatonin acts as an antioxidant and a potent free radical scavenger [7, 9, 17, 18], and provides protective effects on neuronal cells [9, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin, the major secretory product of the pineal gland, has been known to interact with neuroendocrine axis [2] and circadian rhythms [1]. Recently, several studies demonstrated that melatonin acts as an antioxidant and a potent free radical scavenger [7, 9, 17, 18], and provides protective effects on neuronal cells [9, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a chemical mediator produced by the pineal gland and in other tissues. The classical functions of melatonin are associated with the control of the circadian rhythms [1] and the regulation of hypothalamic–pituitary–gonadal axis [2], while other effects of the indole have also been reported [3–6]. Recently, melatonin has been shown to have antioxidant capacity, acting both as a free radical scavenger [7] and a protective agent in neuronal cells [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has accumulated to indicate that melatonin acts on brain to regulate serotoninergic neuro- transmission. For example, alterations in brain serotonin levels have been observed in rats and hamsters after melatonin administration [Anton-Tay et al, 1968;Quay, 1989;Alexiuk and Vriend, 19911. However, these studies have not always yielded similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several reports have described changes in brain serotonin (5-HT) content after alterations of the pineal function or after melatonin administration [Anton-Tay et a]. , 1968; Aldegunde et al, 1985;Vriend, 1989;Quay, 1989;Alexiuk and Vriend, 1991;Steger and Bartke, 19911. In previous studies, we have observed that pinealectomy decreased 5-HT synthesis in some hypothalamic regions and in the amygdala [Miguez et a]., 1991a,b]. In these areas, pinealectomized rats also showed decreased levels of the amine or its acid metabolite, 5-hydroxyindole-3acetic acid (5-HIAA).…”
mentioning
confidence: 99%
“…Melatonin, a bioactive compound secreted primarily by the pineal gland in mammals, possesses a variety of physiological functions including regulating circadian and seasonal rhythms (Quay 1989), removing free radicals, and preventing oxidation of biomolecules (Maldonado et al 2007;Tan et al 2007). Earlier research has revealed that a reduction in melatonin is related to various degenerative diseases such as Alzheimer's disease, HD, and Parkinsonism, and thus this compound has been tested for treating various neurodegenerative disorders (Reiter et al 1999;Srinivasan et al 2005).…”
mentioning
confidence: 99%